Nitrogen fertilization increases the growth and nutritional quality of the forage legume, Calobota sericea – A preliminary investigation. Issue 2 (February 2023) - Britz, Ethan; Cyster, Lilburne; Samuels, Igshaan; Cupido, Clement; Masemola, Letty; Ngcobo, Nothando; Manganyi, Fortune; Müller, Francuois
Abstract: Calobota sericea is being evaluated as a forage for drought stressed areas. The nutritional quality of C. sericea from native populations are poor, and this is believed to be due to poor soil fertility. Therefore, a greenhouse trial was established to determine the impact of N-fertilization level (0, 25, 50, 75 and 100 kg/ha) on the growth and nutritional quality of C. sericea plants. Three-month-old plants were harvested and the root and shoot length, as well as branching intensity on each plant determined. Thereafter, the shoots were separated into leaves and stems and all plant parts were oven dried for dry mass determination. After weighing, the leaves and stems for each plant were combined and the dried shoots used for nutrient determination. Results indicated that increased N application levels is positively correlated with improved C. sericea growth. Similarly, mineral nutrient uptake increased significantly under all the N-fertilization treatments and crude protein content increased from 9.6% to 18.6%. Plant growth was only statistically significantly (p < 0.05) improved when N was applied at rates of 50 kg/ha and more, but crude protein content increased from the lowest N application rates (25 kg/ha). The improved growth and nutrient uptake could primarily be explained by improved resource allocation under N-fertilization. Therefore, appropriately fertilized C. sericea can result in improved forage production and improved quality forages and when N is applied at high enough rates.